The Implementation Of Patient Safety Management In Melati General Hospital, Perbaungan - Nisrina Nisrina (The International Science of Health Journal, 2023)
This study examines the implementation of patient safety management at Melati General Hospital in Perbaungan. Patient safety is a critical component of healthcare quality, aimed at minimizing risks, errors, and harm to patients during the provision of health services. The research utilizes a qualitative approach, involving comprehensive interviews with hospital staff, direct observations, and analysis of hospital safety protocols and records. Key findings reveal that while Melati General Hospital has established several patient safety measures, there are areas needing improvement, particularly in staff training, adherence to safety protocols, and incident reporting systems. The study identifies the strengths and weaknesses of the current patient safety management practices and offers recommendations for enhancing the safety culture within the hospital. Effective implementation of these recommendations is expected to lead to significant improvements in patient safety outcomes, thereby ensuring higher standards of care and patient trust.